Special diets and food allergies - Ballard, carol (Oxford : Heinemann, 2006)
Discusses the importance of making healthy food chooses, looks at the role of food choice in weight control and in handling medical conditions, explains what allergies are, and includes a selection of special recipes.
Keywords: Food allergy -- Diet -- Juvenile literature; Nutrition -- Juvenile literature